Studi Kasus Karakteristik Kepribadian Pasien Skizofrenia Paranoid Ditinjau dari Minnesota Multiphasic Personality Inventory-2 (MMPI-2) - Muna'amah, Rikza Novita; Gunatirin, Elly Yuliandari (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
The personality of paranoid schizophrenia patients is certainly different and has its own peculiarities, therefore, some personality tests are needed so that the diagnosis and application of the intervention can be on target. One of the measuring instruments which widely used is the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). The purpose of this study was to study the personality characteristics of paranoid schizophrenia patients that reviewed with the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). The sampling technique used purposive sampling with one patient. Paranoid schizophrenia has personality characteristics of the type Schizophrenia (Sc) (94 = very high) and Paranoia (Pa) (83 = very high). These patients often have delusions and hallucinations, making it difficult to determine reality and fantasy.